Pengaruh HRM Practices terhadap Employee Performance melalui Job Satisfaction di Industri Makanan dan Minuman - Fatyandri, Adi Neka; Sabella, Delfina Muthia; Muchsinati, Evi Silvana (Universitas Muhammadiyah Palembang, 2024)
This study aims to deepen the understanding of the influence of HRM practices on employee performance, considering job satisfaction as a mediator, and evaluate its effectiveness in the food and beverage industry. The research approach is quantitative, with data collection involving 290 café employees in Batam through an online questionnaire. The data obtained were analyzed using Smart PLS. This study found a significant positive influence on HRM Practices on Employee Performance and Job Satisfaction. However, the positive effect generated by Job Satisfaction on Employee Performance proved to be insignificant, and Job Satisfaction did not act as a mediator in the relationship between HRM Practices and Employee Performance. In the food and beverage industry, companies are advised to concentrate on things that can improve employee performance, such as training, performance appraisals, and compensation.